Auditory Brain Stem Responses in the C57BL/6J Fragile X Syndrome-Knockout Mouse Model - Chawla, Amita; McCullagh, Elizabeth A. (Frontiers in Integrative Neuroscience, 2022)
Sensory hypersensitivity, especially in the auditory system, is a common symptom in Fragile X Syndrome (FXS), the most common monogenic form of intellectual disability. However, linking phenotypes across genetic background strains of mouse models has been a challenge and could underly some of the issues with translatability of drug studies to the human condition. This study is the first to characterize the auditory brainstem response (ABR), a minimally invasive physiological readout of early auditory processing that is also used in humans, in a commonly used mouse background strain model of FXS, C57BL/6J. We measured morphological features of pinna and head and used ABR to measure hearing range, monaural and binaural auditory responses in hemizygous males, homozygous females and heterozygous females compared to wildtype mice. Consistent with previous work we showed no difference in morphological parameters across genotypes or sexes. Male FXS mice had increased threshold for high frequency hearing at 64 kHz compared to wildtype males, while females had no difference in hearing range between genotypes. In contrast, female homozygous FXS mice had decreased amplitude of wave IV of the monaural ABR, while there was no difference in males for amplitudes and no change in latency of ABR waveforms across sexes and genotypes. Lastly, FXS males had increased latency of the binaural interaction component (BIC) at 0 ITD compared to wildtype males. These findings further clarify auditory brainstem processing in FXS by adding more information across genetic background strains allowing for a better understanding of shared phenotypes.